2019
DOI: 10.2478/raon-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

The influence of genetic variability of DNA repair mechanisms on the risk of malignant mesothelioma

Abstract: Background Malignant mesothelioma (MM) is a rare aggressive tumour of mesothelium caused by asbestos exposure. It has been suggested that the genetic variability of proteins involved in DNA repair mechanisms affects the risk of MM. This study investigated the influence of functional polymorphisms in ERCC1 and XRCC1 genes, the interactions between these polymorphisms as well as the interactions between these polymorphisms and asbestos exposure on MM risk. Patients and methods In total, 237 cases with MM and 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…DNA samples of all other subjects had been isolated during previous studies. 44 Genotyping was performed using competitive allele-specific PCR (KASP), the KASP Master mix (LGC, Middlesex, UK) and custom KASP Genotyping Assay (LGC, Middlesex, UK) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…DNA samples of all other subjects had been isolated during previous studies. 44 Genotyping was performed using competitive allele-specific PCR (KASP), the KASP Master mix (LGC, Middlesex, UK) and custom KASP Genotyping Assay (LGC, Middlesex, UK) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, a larger number of 273 malignant mesothelioma patients and 193 controls from the same Slovenian cohort were analysed for four SNPs in two DNA repair genes (ERCC1 rs11615, rs3212986, and XRCC1 rs1799782, rs25487), but only ERCC1 rs3212986 was found to be significantly associated with the risk for malignant mesothelioma. However, this polymorphism was found to have a protective effect as carriers of ERCC1 rs3212986 heterozygous GT or homozygous TT genotypes had a decreased risk of malignant mesothelioma [115].…”
Section: Genes Involved In Dna Repair Mechanismsmentioning
confidence: 97%
“…Carriers of polymorphic ERCC1 rs11615 allele who were exposed to the low level of asbestos had a decreased risk of malignant mesothelioma. Based on these findings, it has been suggested that the genetic variability of DNA repair mechanisms could contribute to the risk of developing of this aggressive cancer [115].…”
Section: Gene-environment Interactions In Asbestos-related Pleural DImentioning
confidence: 99%
See 2 more Smart Citations